Nature-based solutions in agricultural landscapes for reducing tradeoffs between food production, climate change, and conservation objectives - Miralles-Wilhelm, Fernando (Frontiers in Water, 2023)
This paper presents a synthesis of evidence and implementation gaps in the application of nature-based solutions (NbS) in agricultural landscapes that contribute to reduce trade-offs between food production, climate change and conservation objectives.. The literature and data surveyed relies primarily in peer-reviewed sources and is organized around an overview of NbS science and applications in agricultural landscapes in major biomes. To date, the focus of NbS applications in food production has been predominantly for carbon sequestration, water quality, and disaster-risk management objectives while documented examples of NbS benefits in agricultural production are sparse. Conservation applications of NbS appear to show evidence of effectiveness across multiple objectives in biodiversity, land, soil and water. Evidence and analysis of NbS to meet climate change mitigation targets has surged in recent years driven by global community efforts. Overall, considerable scientific work remains to refine and reduce the uncertainty of NbS benefit estimates across production, climate and conservation objectives, and resilience implications. However, delaying implementation of NbS in agricultural landscapes would likely increase the costs to meet agricultural production, climate, conservation and other societally beneficial goals, while degrading the capacity of natural systems to continue to provide these and other ecosystem services.